(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Adolescents are a large and growing segment of the global as well as the own population of a country. To invest in their health and development is actually investing in the greater wellbeing of the country as they constitute the nation’s core resource for renewal and growth. Objective: To identify the risk behaviour, magnitude, sociodemographic, cultural and economic condition along with common health problems, knowledge about health, hygiene and treatment seeking behaviour among rural adolescents. Materials and Methods: This descriptive type of cross sectional study was conducted in Baliati village, Saturia upazilla of Manikganj district and Mohashashi village, Dhamrai upazilla of Dhaka district for a period of three months starting from November 2015 to January 2016. Targeted population was 10 to 19 years of both sexes residing in the study place. The sample size was of 510 adolescents. Non-probability purposive type of sampling was followed for this study. Data was collected on a structured interview schedule containing close ended questions keeping in view the selected variables of the study. Results: In the study, among 510 respondents 35.3% in the 10-12 years age group and majority respondents were males (66.20%). 12.74% were involved in life threatening activities. In most cases they cross busy traffic (20.9%) and quarrel mostly with any issue (23.2%). Only 1.17% adolescents were addicted. Among addicted respondents 66% took Cannabis/ Marijuana. Cause of taking drugs among addicted respondents was by imitating others (83%). Skin disease was observed in 18.6 % respondents. 95.9% adolescents take treatment when they become ill and most of them (53.5%) go to doctors for allopathic treatment. Conclusion: The magnitude of risk behaviours and health problems is a signal to the society, non-government, government and other international organizations that needs timely and appropriate intervention programs. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 102-106